Predicting Risk Factors of Total Hip Arthroplasty Conversion after Concentrated Autologous Bone Marrow Aspirate Transplantation for the Treatment of Idiopathic Osteonecrosis of the Femoral Head: A Retrospective Review of 213 Hips at a Mean Follow-up of 5 Years - Hyodo, Kojiro; Yoshioka, Tomokazu; Sugaya, Hisashi; Akaogi, Hiroshi; Aoto, Katsuya; Wada, Hiroshi; Shimizu, Yukiyo; Yamazaki, Masashi; Mishima, Hajime (The Journal of Hip Surgery, 2017)
To identify the predictive risk factors of total hip arthroplasty (THA) conversion after concentrated autologous bone marrow aspirate transplantation (CABMAT) as a hip joint–preserving surgery for idiopathic osteonecrosis of the femoral head (ONFH). We retrospectively reviewed 123 patients (213 hips; 65 men [115 hips]) who underwent CABMAT (average age: 40 years) between April 2003 and December 2010. The mean follow-up period was 61 months. Of 213 hips, 144 had corticosteroid-associated ONFH, 46 had alcohol-associated ONFH, and 23 had no identifiable etiological factors. We investigated age; sex; body mass index (BMI); history of using bisphosphonates, steroids, and proton pump inhibitors; etiologic factors; preoperative disease classification and staging; Japanese Orthopedic Association clinical score; and various clinical data. Multivariate logistic regression analysis was performed to analyze the data. Of 213 hips, 51 (23.9%) were converted to THA. The conversion rates were 18.6% in the precollapse group (stages 1 and 2) and 30.0% in the postcollapse group (stages 3–4). The conversion rate to THA was 0% in patients with the preoperative disease types A and B. Moreover, treatment in 62.5% of patients in stage 4 was converted to THA. In multivariate logistic regression analysis, the disease type, BMI, history of bisphosphonates use, hospitalization duration, and age were significantly correlated with conversion to THA. The largest THA conversion predictive factor was the type C2. The preoperative disease type, BMI, and history of bisphosphonates use can predict conversion to THA and suggest which patients with idiopathic ONFH are appropriate for CABMAT treatment. Our new marrow concentration method for CABMAT improves the reliability of hip preserving surgery, and further research is warranted.
Keywords: bone marrow aspirate; joint-preserving surgery; osteonecrosis of the femoral head; total hip arthroplasty